2002
DOI: 10.1074/jbc.m111086200
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin Variants Display Differential Binding Characteristics for the Phosphorylated N-Formyl Peptide Receptor Carboxyl Terminus

Abstract: The phosphorylation-dependent binding of arrestins to cytoplasmic domains of G protein-coupled receptors (GPCRs) is thought to be a crucial step in receptor desensitization. In some GPCR systems, arrestins have also been demonstrated to be involved in receptor internalization, resensitization, and the activation of signaling cascades. The objective of the current study was to examine binding interactions of members of the arrestin family with the formyl peptide receptor (FPR), a member of the GPCR family of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…However, we have also shown that neither truncated arrestin-2 nor arrestin-3 exhibits specific binding to the nonphosphorylated FPR carboxyl terminus alone (30). Together, these results support a role for additional receptor domains in arrestin binding.…”
Section: Effects Of Truncated Arrestin-2 On the Phosphorylated Wildmentioning
confidence: 55%
See 1 more Smart Citation
“…However, we have also shown that neither truncated arrestin-2 nor arrestin-3 exhibits specific binding to the nonphosphorylated FPR carboxyl terminus alone (30). Together, these results support a role for additional receptor domains in arrestin binding.…”
Section: Effects Of Truncated Arrestin-2 On the Phosphorylated Wildmentioning
confidence: 55%
“…1 The abbreviations used are: GPCR, G protein-coupled receptor; FPR, N-formyl peptide receptor; GTP␥S, guanosine 5Ј-3-O-(thio)triphosphate; GFP, green fluorescent protein; FITC, fluorescein 5-isothio-phosphorylation-and activation-independence with a number of GPCRs, including receptors from which the carboxyl terminus, containing critical phosphorylation sites, has been removed (25). We have recently demonstrated that the affinity of truncated arrestin-2 for a carboxyl-terminal peptide of the Nformyl peptide receptor (FPR) is significantly higher than that of wild type arrestin-2 (30). Thus, it is likely there is a complex interplay of multiple receptor and arrestin domains.…”
mentioning
confidence: 99%
“…The carboxyl terminus of FPR (as well as of other GPCRs) contains serine and threonine residues that may be phosphorylated by various kinases. Removal of eight possible phosphorylation sites in the cytoplasmic tail of FPR has been shown to block ligand-induced phosphorylation of the receptor, a loss that correlates to a lack of receptor desensitization and receptor internalization (39). These two processes are regulated separately, illustrated by the fact that an inability to phosphorylate some residues (but not others) completely abolishes receptor desensitization but is without effect on internalization (40).…”
Section: Discussionmentioning
confidence: 99%
“…The studies of arrestin interactions with receptor elements using surface plasmon resonance also yielded micromolar affinities (Cen et al, 2001a;Liu et al, 2004). Wild-type arrestins bound to the immobilized phosphorylated C-terminal peptide of the N-formyl peptide receptor with micromolar affinities, although several constitutively active mutants demonstrated submicromolar dissociation constants (Potter et al, 2002). Interestingly, in a few studies where the affinity of arrestin proteins for the native phosphoreceptor has been measured, it was found to be nanomolar for rhodopsin (Schleicher et al, 1989;Pulvermuller et al, 1997;Osawa et al, 2000) and sub-nanomolar for the b2AR or m2 muscarinic cholinergic receptor (Gurevich et al, 1993a(Gurevich et al, , 1995.…”
Section: Receptor Elements Implicated In Arrestin Bindingmentioning
confidence: 99%